ORANGE family proteins: multifunctional chaperones shaping plant carotenoid level, plastid development, stress tolerance, and more - Emalee Wrightstone; Lilin Xu; Sombir Rao; Abhijit Hazra; Li Li (Molecular Horticulture)
Abstract ORANGE (OR) family proteins are DnaJE1 molecular chaperones ubiquitous and highly conserved in all plant species, indicating their important roles in plant growth and development. OR proteins have been found to exert multiple functions in regulating carotenoid and chlorophyll biosynthesis, plastid development, and stress tolerance, with additional functions expected to be discovered. As molecular chaperones, OR proteins directly influence the stability of their target proteins via their holdase activity and may perform other molecular roles through unknown mechanisms. Exploration of OR has uncovered novel mechanisms underlying core plant metabolism pathways and expanded our understanding of processes linked to plastid development. Continued investigation of OR family proteins will not only reveal new functions of molecular chaperones but also provide pioneering tools for crop improvement. Thus, OR family proteins offer a distinctive opportunity to comprehend molecular chaperones in modulating various metabolic and developmental processes and exemplify the importance of chaperones in crop development and adaptability. This review briefly details the history of OR family proteins, highlights recent advancements in understanding their myriad of functions, and discusses the prospects of this fascinating group of chaperones towards generating innovative, more nutritious, and resilient crops alongside other agronomically important traits.